The influence of psychological flexibility on persistent post concussion symptoms and functional status after mild traumatic brain injury. Issue 7 (27th March 2023) - Faulkner, Josh W.; Snell, Deborah L.; Theadom, Alice; Mahon, Susan; Barker-Collo, Suzanne
Abstract: Purpose: This study investigated the predictive role of psychological flexibility on long-term mTBI outcomes. Method: Adults with mTBI ( N  = 147) completed a context specific measure of psychological flexibility, (AAQ-ABI), psychological distress, and mTBI outcomes at less than three months post injury (M = 6.02 weeks after injury) and 6 months later ( N  = 102). Structural equation modelling examined the mediating effects of psychological flexibility on psychological distress and mTBI outcomes at six months. The direct effect of psychological flexibility at less than three months on mTBI outcomes at six months was entered into the model, plus pre-injury and injury risk factors. Results: The theoretically derived model had good overall fit (χ2 = 1.42; p  = 0.09; NFI = 0.95; TLI = 0.95; CFI = 0.98 and RMSEA = 0.06). Psychological flexibility at less than 3 months was directly significantly related to psychological distress and post-concussion symptoms at six months. Psychological flexibility at 6 months significantly mediated the relationship between psychological distress and functional disability but not post-concussion symptoms at six months post injury. Conclusion: The exploratory findings suggest that a context specific measure of psychological flexibility assessed acutely and in the chronic phase of recovery may predict longer-term mTBI outcomes. Implications for Rehabilitation: Persistent post-concussion symptoms (PPCS) after mild traumatic brain injury (mTBI) can have a significant impact on wellbeing, functional status, and quality of life. In this study, psychological flexibility early in recovery, was associated with higher levels of psychological distress and more severe post-concussion symptoms six months later. Psychological flexibility at six months post-injury also mediated the relationship between psychological distress and functional disability. A context specific measure of psychological flexibility may predict poorer long-term outcomes following mTBI.